Association between Urinary N-Acetyl-Beta-D-Glucosaminidase and Microalbuminuria in Diabetic Black Africans - Francis Patrick Udomah; Udeme Ekpenyong Ekrikpo; Emmanuel Effa; Babatunde Salako; Ayodeji Arije; Solomon Kadiri (International Journal of Nephrology)
Diabetes mellitus is the commonest cause of ESRD worldwide and third most common cause in Nigeria. Recent reports from Nigeria indicate the prevalence of diabetic nephropathy as an aetiology of ESRD is increasing necessitating early diagnosis of diabetic nephropathy. We measured the urinary excretion of N-acetyl-beta-D-glucosaminidase (NAG), NAG/creatinine ratio, urinary protein-creatinine ratio and calculated eGFR in 30 recently diagnosed nonhypertensive diabetics and 67 controls. The age and sex distribution, systolic blood pressure, serum and urinary creatinine were similar for both groups. There was higher urinary excretion of NAG (304 versus 184 μmol/h/L, 𝑃<0.001) and NAG/creatinine ratio (21.2 versus 15.7 μmol/h/L/mmolCr, 𝑃<0.001) in the diabetics than controls. There was a strong correlation between NAG/creatinine ratio and albumin/creatinine ratio (𝑟=0.74, 𝑃<0.001). A multivariate linear regression model showed a significant linear relationship between NAG/creatinine ratio and albumin/creatinine ratio after adjusting for the effect of blood pressure, age, sex, and serum creatinine. The strong association found between albumin/creatinine ratio and NAG/creatinine ratio perhaps indicates the need for further investigation of the clinical utility of NAG/creatinine ratio as a screening tool for early nephropathy in African diabetics.